Emergence of plasmid mediated carbapenemase OXA-48 in a Klebsiella pneumoniae strain in Algeria. Issue 4 (December 2014) - Aggoune, Nadjet; Tali-Maamar, Hassiba; Assaous, Farida; Benamrouche, Nabila; Naim, Malek; Rahal, Kheira
Abstract: A carbapenem resistant Klebsiella pneumoniae strain was isolated in October 2011 in the pediatric unit of the Hôpital central de l'armée in Algeria, this strain have been confirmed for the production of OXA-48 carbapenemase. The bla OXA-48 gene was located on a self conjugative plasmid of 70 kb. Multilocus sequence typing indicated the presence of the sequence type ST-307. This is the first isolation of OXA-48-producing K. pneumoniae in Algeria.